A brief account on ocular graft versus host disease - Debapriya Chatterjee (Indian Journal of Ophthalmology, 2023)
The incidence of ocular graft versus host disease (oGVHD) is rising due to the increasing numbers of bone marrow transplantations for various hematologic malignancies and non-malignant indications. The ophthalmic aspect of graft versus host disease (GVHD) still requires much understanding. We carried out a PubMed search of all articles using the terms “oGVHD,” “dry eye + hematopoietic stem cell transplantation (HSCT),” “acute GVHD,” and “Chronic GVHD.” The review mainly focuses on the existing lacunae in terms of diagnostic criteria. Diagnosis of ocular involvement in GVHD follows the criteria described by the National Institute of Health Consensus Conference (NIH CC) or International Chronic oGVHD (ICCGCHD) consensus group. The severity grading of oGVHD is by Jab's or Robinson's grading for conjunctival involvement. NIH CC and ICCGVHD remain the most commonly used scoring systems. Management of ocular involvement during acute GVHD remains challenging, whereas chronic oGVHD in its milder forms mainly manifests as dry eye disease and is treated accordingly. Multiple unanswered questions remain regarding this entity's pathogenesis, diagnostic criteria, and clinical features. Large-scale prospective studies involving oncologists and ophthalmologists must answer questions and formulate guidelines.